Sosialisasi Pelatihan Permainan Tonnis bagi Guru Penjaskesrek di Kabupaten Sarmi sebagai Upaya Peningkatan Kualitas Profesi - Ewendi W Mangolo; Ince Abdul Muhaemin Mangngassai; Marsuki Marsuki; Andi Syaiful (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
This Community Service activity aims to socialize tonnis games for physical education, sports and health teachers (Penjasorkes) in Sarmi Regency. The boundaries of the field and the high cost of infrastructure in learning small ball games in schools are one of the reasons teachers have to innovate to develop an easy and cheap game model, namely tonnis games. The method used in this devotion uses the lecture method, the question and answer method, demonstrations to demonstrate tonnis game skills, and hands-on practice to practice the basic skills of tonnis games as a whole. The training participants were 20 teachers from elementary schools, junior high schools, high schools/ vocational schools in Sarmi Regency. The activity was held twice, namely on September 6, 7, 2022. At the end of the program, an evaluation is carried out to find out the mastery and skills of participants in the tonnis game. The results of the activity showed that in general the implementation of the training went smoothly. The mastery of the Penjaskesrek teachers towards the basic techniques of tonnis games is relatively good. The response of the participating teachers was positive and they were very enthusiastic about participating in the socialization and training. The obstacle encountered in the implementation of training is the lack of time to practice tonnis games